Postnatal depression and anxiety screening and management by maternal and child health nurses in community settings: A scoping review. (September 2021) - Arefadib, Noushin; Cooklin, Amanda; Nicholson, Jan; Shafiei, Touran
Highlights: Maternal and child health nurses face challenges in screening and managing postnatal depression and anxiety. Individual and organisational factors contribute to a gap between best practice and clinical practice. Addressing this provides a valuable road map for future policy and practice strategies and guidelines. Abstract: Objective: To examine the range and nature of primary research evidence on postnatal depression and anxiety screening and management by maternal and child health nurses within community settings. Background: Maternal and child health nurses are well-placed to identify and support women at risk of, or experiencing, postnatal depression and anxiety- a prevalent public health issue which remains largely undetected. Methods: Scoping methodology, guided by the Arksey and O'Malley (2005) framework, was used. The following electronic databases were searched in June 2019 and again in July 2020: Cumulative Index of Nursing and Allied Health Literature, MEDLINE, PsycINFO, and COCHRANE Library. Primary studies that were published in English, between 2008 and 2020, were included. PRISMA checklist and PRISMA flow diagram were used to adhere to best practice guidelines. Results: Twenty-three articles, relating to 22 studies, met the inclusion criteria. Two principal themes were identified: 'screening for postnatal depression and anxiety' and 'factors that influence postnatal depression and anxiety management'. Subthemes in the former related to attitudes toward screening, routine screening practice, screening efficacy, and attitudes toward the Edinburgh Postnatal Depression Scale. Subthemes in the latter included availability of formal care pathways, referral options, knowledge and confidence, and multiagency collaboration. Conclusions and relevance to clinical practice: While maternal and child health nurses value their role in identifying and supporting mothers at risk of postnatal depression and anxiety, certain individual and organisational factors contribute to a gap between best practice and clinical practice. Narrowing the gap between evidence and practice is unlikely without directly addressing these barriers. Gaps in maternal and child health nurses' knowledge, skills and confidence regarding effective screening and management of mothers experiencing, or at risk of, postnatal depression and anxiety, impacts the quality of care provided. Ongoing training and professional development which adequately addresses these gaps is required.